Accelerated aging of fast pyrolysis bio-oil: a new method based on carbonyl titration. Issue 17 (9th March 2020) - Black, Stuart; Ferrell, Jack R.
Abstract : Fast pyrolysis bio-oils are known to age upon storage at room temperature, resulting in changes to both physical properties (increase in viscosity) and chemical composition (decrease in carbonyl content). Abstract : Fast pyrolysis bio-oils are known to age upon storage at room temperature, resulting in changes to both physical properties (increase in viscosity) and chemical composition (decrease in carbonyl content). A widely used accelerated aging test consists of holding samples at 80 °C for 24 hours, with viscosity measurement before and after heat treatment. Unfortunately, the viscosity measurement has high variability, and cannot be applied to samples that have phase separated. Here, we show that carbonyl content is a much better metric for tracking bio-oil aging. Furthermore, results from different accelerated aging protocols (for varying times at both 40 °C and 80 °C) are compared to actual room temperature storage for over 3 years. Based on this, we show that the accepted accelerated aging test (80 °C for 24 hours) is too severe a treatment, and results in more extensive aging than would occur with over 3 years of storage at room temperature. A new aging protocol is proposed: heat treatment at 80 °C for 2 hours, with carbonyl quantification before and after. This protocol correlates to room temperature storage for 1–3 months. Finally, samples were also kept in cold storage (at both 9 °C and −17 °C) for over 3 years. Unexpectedly, these samples also showed a substantial reduction in carbonyl content (by up to 25%), indicating that bio-oil aging still progresses at low temperatures. Both physical and chemical changes will occur in samples in cold storage, which has implications for the archiving of bio-oil samples.